2017
DOI: 10.1016/j.biopsych.2016.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in a Unique Class of Cortical Chandelier Cell Axon Cartridges in Schizophrenia

Abstract: Background The axons of chandelier cells (ChCs) target the axon initial segment (AIS) of pyramidal neurons, forming an array of boutons termed a cartridge. In schizophrenia, the density of cartridges detectable by GABA membrane transporter-1 (GAT1) immunoreactivity is lower, whereas the density of AISs detectable by immunoreactivity for the α2 subunit of the GABA-A receptor is higher in layers 2-superficial 3 of the prefrontal cortex (PFC). These findings were interpreted as compensatory responses to lower GAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 57 publications
0
41
0
Order By: Relevance
“…The striking selectivity of ChC innervation at the AIS of PyNs has intrigued neuroscientists ever since the initial discovery of ChCs in the 1970s (Jones, 1975;Somogyi, 1977;Szentá gothai and Arbib, 1974). This interest has heightened with accruing evidence showing that this unique form of subcellular innervation allows ChCs to exert powerful yet precise control over cortical PyN spiking and population output (Howard et al, 2005;Inan and Anderson, 2014;Lu et al, 2017) and, in particular, given increasing reports linking ChC connectivity defects to neurological conditions, such as schizophrenia and epilepsy (Ariza et al, 2018;Del Pino et al, 2013;Lewis, 2011;Ribak, 1985;Rocco et al, 2017). Despite these findings, little to nothing is known about the mechanisms underlying the subcellular innervation of neocortical PyN AISs by ChCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The striking selectivity of ChC innervation at the AIS of PyNs has intrigued neuroscientists ever since the initial discovery of ChCs in the 1970s (Jones, 1975;Somogyi, 1977;Szentá gothai and Arbib, 1974). This interest has heightened with accruing evidence showing that this unique form of subcellular innervation allows ChCs to exert powerful yet precise control over cortical PyN spiking and population output (Howard et al, 2005;Inan and Anderson, 2014;Lu et al, 2017) and, in particular, given increasing reports linking ChC connectivity defects to neurological conditions, such as schizophrenia and epilepsy (Ariza et al, 2018;Del Pino et al, 2013;Lewis, 2011;Ribak, 1985;Rocco et al, 2017). Despite these findings, little to nothing is known about the mechanisms underlying the subcellular innervation of neocortical PyN AISs by ChCs.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, recent studies have shown a critical role for ChCs in the synchronization of firing patterns of large populations of PyNs in different functional states (Glickfeld et al, 2009;Lu et al, 2017;Viney et al, 2013;Woodruff et al, 2011;Zhu et al, 2004). The importance of proper ChC function is further underscored by the association of ChC connectivity defects with brain disorders such as schizophrenia, epilepsy, and autism spectrum disorder (Ariza et al, 2018;Del Pino et al, 2013;Lewis, 2011;Ribak, 1985;Rocco et al, 2017). To date, however, the molecular mechanisms governing neocortical ChC/PyN AIS innervation remain entirely unknown.…”
Section: Introductionmentioning
confidence: 90%
“…Based on translation of brain development milestones, the early time point of induction (E9.5) overlaps with the first trimester of human pregnancy [47] as well as with the onset of neurogenesis of cortical GABAergic interneurons [85]. Given the significant evidence for impairment of cortical GABAergic interneurons in human postmortem brain studies of patients with mental illness [86][87][88], the dysfunction of developmental programs for GABAergic interneurons might have causative effect on cognitive phenotype of the patients. Further studies of GABAergic circuitry development in environmental and genetic mouse models mimicking human developmental insults will reveal commonalities and differences in the affected subtypes of GABAergic interneurons across all developmental processes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on translation of brain development milestones, the early timepoint of induction (E9.5) overlaps with the first trimester of human pregnancy 47 as well as with the onset of neurogenesis of cortical GABAergic interneurons86 . Given the significant evidence for impairment of cortical GABAergic interneurons in human postmortem brain studies of patients with mental illness[87][88][89] , the dysfunction of developmental programs for GABAergic interneurons might have causative effect on cognitive phenotype of the patients. Further studies of GABAergic circuitry development in environmental and genetic mouse models mimicking human developmental insults will reveal commonalities and differences in the affected subtypes of GABAergic interneurons across all developmental processes.…”
mentioning
confidence: 99%